Evaluation of information presented within mast cell tumour histopathology reports in the United States: 2012–2015. Issue 3 (7th June 2018) - Reagan, Jennifer K.; Selmic, Laura E.; Fallon, Caroline; Driskell, Elizabeth A.; Garrett, Laura D.
Abstract: For canine mast cell tumour (MCT), histopathology reports are one of the main factors considered in the decision‐making process regarding need and type of adjunctive therapy. However, considerable variation exists in types of information reported, especially relating to surgical margins. The purpose of this study was to describe and evaluate how information is presented within canine MCT histopathology reports across the United States. The reports were collected from medical and surgical oncologists from 4 geographic regions of the USA: Midwest, Northeast, South and West. All reports were obtained between January 1st 2012 and May 1st 2015. Inclusion criteria required that the final diagnosis was MCT, a microscopic description was present, and it was not a scar revision. Three hundred and sixty‐eight reports were collected from 26 contributors. While the majority of the reports contained a clinical history (85.9%), information for certain prognostic indicators such as location and mass size was lacking. Grading with both Patnaik and Kiupel systems were described in 76.5% of reports with a single system being used in 7.1% and 15.2% of reports, respectively. Subcutaneous MCT were assigned a grading scheme in 67.2% of reports with 33.3% stating appropriate limitations. Surgical margins were reported in 92% of the reports with 77.2% describing deep and lateral margins separately. Tissue composing the deep margin was only described in 10.9% of the reports. The present results indicate reporting of MCT has variability across pathologists with inconsistencies present in the reporting of clinical history, margin evaluation and subcutaneous MCT grading. Abstract : An investigation was performed to assess the extent of variability in reporting for histopathology of canine mast cell tumour.